The impact of Emotional Intelligence on Role Conflict: Case Study at The National Social Security Fund in Laghouat - Linani Hadjer; Hamdi Aboulkacem (جامعة عمار ثليجي الاغواط, 2022)
The study aims to identify the impact of emotional intelligence on role conflict among working mothers at the National Social Security Fund in Laghouat. To achieve the objectives of the study: A questionnaire was developed for the purpose of collecting information and data from the study sample, which was 40 working mothers, Where the method was used the structural equations modeling by (Smartpls) software. The study concluded that there is a statistically significant impact of emotional intelligence on role conflict among working mother at the National Social Security Fund in Laghouat. As well as there is a statistically significant impact of the dimensions of self-awareness and self-motivation on role conflict among working mothers at the National Social Security Fund in Laghouat. and there is no statistically significant impact of the dimension Self Emotion Regulation and Social-awareness on role conflict among working mothers at the National Social Security Fund in Laghouat. despite that there is no statistically significant differences of emotional intelligence among working mothers at the National Social Security Fund in Laghouat, are due to (Age, number of children, educational level, hierarchal level, experience and living), and there is statistically significant differences of role conflict among working mothers at the National Social Security Fund in Laghouat, are due to (Living).